Teachers’ Perception On Digital Media Technology - Thanavathi, Dr.C. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Teacher education institutions are faced with the challenge of preparing a new generation of teachers to effectively use the new learning tools in their teaching practices. Education in India faces a number of problems. These problems include the shortage of qualified teachers, very large student population, high dropout rates of teachers, students, and weak curricula. All of these negative aspects result in poor delivery of education. The most obvious technique for professional development of teacher is to provide basic Digital Technology knowledge and skills. It is necessary for teachers to become skilled in operating the new technologies and in exploiting them effectively as educational tools. Teachers must master the use of digital media technology skills of research, critical analysis, linking diverse types and sources of information, and reformulating retrieved data